2011
DOI: 10.1002/emmm.201100173
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of T cells during persistent Staphylococcus aureus infection: from antigen‐reactivity to in vivo anergy

Abstract: Staphylococcus aureus is an important human pathogen that can cause long-lasting persistent infections. The mechanisms by which persistent infections are maintained involve both bacterial escape strategies and modulation of the host immune response. So far, the investigations in this area have focused on strategies used by S. aureus to persist within the host. Here, we used an experimental mouse model to investigate the host response to persistent S. aureus infection. Our results demonstrated that T cells, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
86
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 48 publications
(72 reference statements)
4
86
0
1
Order By: Relevance
“…Notably, TLRinduced B cell-derived IL-10 production interferes with Ag presentation and T cell activation in a Salmonella infection model (54). Well in line with these findings T cell hyporesponsiveness was recently described in a murine model for chronically persistent S. aureus infection (71), although the exact mechanism promoting T cell anergy remained obscure. Of note, unselective differentiation of B cells into short-lived plasmablasts mainly induces the production of unspecific IgM (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, TLRinduced B cell-derived IL-10 production interferes with Ag presentation and T cell activation in a Salmonella infection model (54). Well in line with these findings T cell hyporesponsiveness was recently described in a murine model for chronically persistent S. aureus infection (71), although the exact mechanism promoting T cell anergy remained obscure. Of note, unselective differentiation of B cells into short-lived plasmablasts mainly induces the production of unspecific IgM (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In a systemic model of chronic S. aureus bloodstream infection, kidney abscesses were still apparent on day 56 postinfection due to impaired T cell responses (20); subsequently, this immunosuppression was attributed to the expansion of myeloid-derived suppressor cells (MDSCs) and to a lesser extent Tregs in the spleens of infected mice compared with uninfected controls (21). Although both IL-10 and TGF-b were produced, immunosuppression was primarily dependent on cell-cell contact that inhibited effector T cell responses (21).…”
mentioning
confidence: 99%
“…The smallcolony variants can later revert to the full virulent wild-type phenotype, a feature that can explain the recurrence of certain S. aureus infections months or even years after their apparent elimination (12). Recently, we reported that T cells play a protective role during S. aureus infection, but they lose their ability to respond to bacterial Ags with the transition from acute infection to persistence, and they exhibit a dysfunctional state that may explain their failure to promote sterilizing immunity (13). The failure to sustain T cell responsiveness could represent a major driving force for the development of S. aureus chronic infection.…”
mentioning
confidence: 99%